Теорія фітогенного поля: становлення, сучасний стан, перспективи розвитку - Gorelov, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The main stages of the begining, modern state and development perspectives of the phytogenic field theory are considered. The main terms, methodical ways of the investigation of this phenomenon, the role and the meaning in different sites of plant life activity and their society are given. The necessity of the further development of the phytogenic field theory, its informational, structure-forming and communicative aspects is grounded.